Use of Solid Monoblock Rib cartilage Graft for Augmentation Rhinoplasty in Tertiary Care Centre: A Prospective Study - Mahato, Nain Bahadur; Pradhan, Sujan; Neupane, Prajwol; Neupane, Shristi; Pradhan, Rosi (Journal of Institute of Medicine Nepal, 2025)
Introduction Autologous rib cartilage is commonly used graft material for major dorsal augmentation, especially in asian rhinoplasty, however, concern persists regarding warping and donor-site morbidity. This study aims to evaluate the aesthetic satisfaction and complications associated with autologous rib cartilage grafts in augmentation rhinoplasty. Methods This prospective observational study was conducted at the Department of Ear, Nose, and Throat of Kathmandu Medical College from April 2023 to March 2025. Fifty-six patients aged between 18 to 50 years with severe saddle nose deformity either due to congenital or traumatic nasal malformations were included. Patients with nasal polyposis or granulomatous diseases were excluded. Primary outcome was evaluated by using Rhinoplasty Outcome Evaluation (ROE) score (0-24 scale) pre, 6 months and 1 year postoperatively. Secondary outcome included complication rates. Results A total of 56 patients (mean age 31.63 ± 5.68 years; 53.6% female) were included, with congenital abnormalities constituting of 80.4%. Mean ROE scores improved from 8.13 ± 1.74 preoperatively to 18.02 ± 1.22 at 6 months and 18.40 ± 2.15 at 1 year postoperatively (p<0.001). Graft-related complications were warping occurring in 2 cases (3.57%) and graft displacement in 1 case (1.79%). Donor-site morbidity included hypertrophic scar in 2 cases (3.57%) and persistent donor-site pain in 1 case (1.79%). No infections, graft extrusions, or pneumothorax were observed. Conclusion By using solid autologous costal cartilage graft, good patient satisfaction, and minimal donor-site complications can be achieved.